Arboviral Surveillance among Pediatric Patients with Acute Febrile Illness in Houston, Texas - Sahni, Leila C. (Am J Trop Med Hyg, 2018)
We instituted active surveillance among febrile patients presenting to the largest Houston-area pediatric emergency department to identify acute infections of dengue virus (DENV), West Nile virus (WNV), and chikungunya virus (CHIKV). In 2014, 1,063 children were enrolled, and 1,015 (95%) had blood and/or cerebrospinal fluid specimens available for DENV, WNV, and CHIKV testing. Almost half (49%) reported recent mosquito bites, and 6% (N = 60) reported either recent international travel or contact with an international traveler. None were positive for acute WNV; three had false-positive CHIKV results; and two had evidence of DENV. One DENV-positive case was an acute infection associated with international travel, whereas the other was identified as a potential secondary acute infection, also likely travel-associated. Neither of the DENV-positive cases were clinically recognized, highlighting the need for education and awareness. Health-care professionals should consider the possibility of arboviral disease among children who have traveled to or from endemic areas.